Relationship between mothers'/caregivers' reported learning difficulty and internalizing symptoms (anxiety and depression) of children aged 5–17 years in Ghana. (December 2021) - Norman, Queen Angela; Dey, Nutifafa Eugene Yaw; Owusu Ansah, Kenneth; Arthur-Holmes, Francis; Duah, Henry Ofori; Agbadi, Pascal
Highlights: Children with learning difficulties in Ghana were associated with higher likelihood of experiencing anxiety and depression. Approximately 5% of Ghanaian children aged 5−17 years had learning difficulties. Approximately 4% and 3% of Ghanaian children aged 5−17 years experienced anxiety and depression daily, respectively. Abstract: Background: Children with learning difficulties are vulnerable to internalizing symptoms, particularly anxiety and depression. However, only few studies have examined this relationship in low-and-middle-income countries using a nationally representative data. Aims: This study aimed to examine the relationship between learning difficulty and internalizing symptoms of children aged 5−17 years in Ghana while controlling for covariates. Methods and procedures: We analyzed children's data using mothers'/caregivers' reports from the 2017/2018 Ghana Multiple Indicator Cluster Survey Six (MICS 6). Data of 8, 958 children aged 5−17 years were used for the analysis. Outcomes and results: About 20% of the children had some learning difficulties whereas 5% could not learn at all. Learning difficulty was associated with symptoms of anxiety and depression of children. Specifically, children who had some learning difficulties had higher odds of feeling anxious [APOR = 1.28, 95% CI:1.11, 1.49, p = 0.001] while those with some difficulties [APOR=1.24, 95% CI:1.07, 1.44, p = 0.004] and a lot of difficulties or could not learn at all [APOR=1.74, 95% CI:1.28, 2.37, p < 0.01] had higher odds of feeling depressed. Conclusion and implications: The findings call on stakeholders in education and health to prioritize the mental health of all school-going children, particularly those with learning difficulties in Ghana.